Sustainable Materials in Architectural Design: Case Studies of Carbon- Neutral Buildings - Krishan Rana (International Journal of Architectural Design and Planning, 2024)
The architectural sector is under growing pressure to lower its carbon footprint, mainly by reconsidering material selections, as the need to slow down climate change becomes more pressing. With an emphasis on creative material uses in numerous international architectural projects, this review article examines the vital role that sustainable materials play in creating carbon-neutral buildings. The need for alternative, low-carbon materials that may accomplish comparable performance levels with a less environmental effect is growing as a result of the substantial greenhouse gas emissions from traditional building materials like steel and cement. This study looks at sustainable choices that can reduce emissions over a building's lifecycle, such as bio composites, low-carbon concrete, recycled metal, and reused wood. The study presents real-world uses for these materials and assesses how well they work to achieve carbon neutrality and improve urban resilience through a thorough examination of a few case studies, including Powerhouse Brattørkaia in Norway and the Bullitt Centre in the United States. The environmental, economic, and social effects of sustainable materials are also included in this review, along with the difficulties and constraints that presently prevent their broad use. Supply chain problems, technical limitations, and cost ramifications are assessed as important obstacles, along with possible ways to overcome them. The results of these case studies highlight how sustainable materials have the potential to make a substantial contribution to resource conservation, carbon reduction, and energy savings. Recommendations for incorporating sustainable materials into architectural processes are included in the paper's conclusion. These include improved research collaboration, policy support, and lifetime evaluation techniques. These tactics are essential for architects and legislators who want to assist the transition to more resilient, environmentally friendly, and carbon-neutral buildings by fostering a built environment that supports global climate goals.
Keywords: Bio-composites; architectural design; carbon-neutral buildings; low-carbon construction; sustainable materials